Nilai Aplikasi Pendidikan Teknohumanistik Dalam Membangun Sekolah Berbasis Pendidikan Karakter - Ni Komang Rina Yuliasmini (Cetta: Jurnal Ilmu Pendidikan, 2018)
The background of this literature review is the existence of morality problems in education in Indonesia. One solution to the problem is Teknohumanistik education in building a school based on character education. Technohumanistic education covers three important components: science-technology, policy and virtue which is the realization of character education. Education of good is the basis of democracy. Education on values ​​in the framework of character formation of learners need to be effected because of the various negative influences that can affect the behavior of learners such as the tendency of deviant behavior of learners. Technohumanistic education based on character education is very relevant applied in the world of education, especially for schools to improve and nurture good character and moral for all citizens of school. This is inseparable because the breath of the teknohumanistik education is character education.